2020
DOI: 10.3126/jgmcn.v13i2.31166
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risk, preventive behavior and enabling environment among health workers during COVID-19 pandemic in Nepal: an Online Survey

Abstract: Introduction: Perceived risk, preventive behavior and enabling environment play vital role to prevent COVID-19 transmission in health care settings. The study aimed to assess perceived risk, preventive behavior and enabling environment among healthcare workers of different cadre during COVID-19 pandemic in Nepal. Methods: A cross sectional online survey was conducted among 427 health workers from April 25 to June 10, 2020. A structured questionnaire was prepared in Google form. Perceived risk was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…It is consistent with our study that older people in eastern Nepal showed greater fear of COVID-19 (Yadav et al, 2021). According to a survey of Nepalese healthcare professionals, their perception of the risk of COVID-19 is higher than that of our study participants (Sharma et al, 2020). Possibly, health workers know more about COVID-19, which might account for this difference.…”
Section: Discussionsupporting
confidence: 90%
“…It is consistent with our study that older people in eastern Nepal showed greater fear of COVID-19 (Yadav et al, 2021). According to a survey of Nepalese healthcare professionals, their perception of the risk of COVID-19 is higher than that of our study participants (Sharma et al, 2020). Possibly, health workers know more about COVID-19, which might account for this difference.…”
Section: Discussionsupporting
confidence: 90%
“…Fear about infecting family members was high among Nepali healthcare workers in April 2020 (83.6%) [17]. From April to June 2020, perceived risk of COVID-19 was high and access to protective equipment was limited among healthcare workers in Nepal [18]. However, little is known about the extent of COVID-19 worry, mitigation behaviours and concerns among the general population in Nepal.…”
mentioning
confidence: 99%
“…Another study from Spain found a significant relationship between socio-demographic factors and risk perception (Mansilla Domínguez et al, 2020). An online study in Nepal in 2020 noted that the perceived risk of COVID-19 was high for health workers (Sharma et al, 2020).…”
Section: Discussionmentioning
confidence: 99%